2019
DOI: 10.1139/apnm-2018-0671
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine supplementation promotes small to moderate improvements in performance tests indicative of in-game success in professional female basketball players

Abstract: The aim of this study was to determine the effect of acute caffeine supplementation on anaerobic performance in professional female basketball players. A double-blind, placebo-controlled, experimental design was used in a randomized counterbalanced manner. In separate sessions, 10 professional basketball players ingested caffeine (3 mg/kg body mass) or a placebo (dextrose: 3 mg/kg body mass) 60 min before completing countermovement jumps (CMJ) with and without arm swing, a squat jump (SJ), the Lane Agility Dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 50 publications
4
76
2
Order By: Relevance
“…Although we have not directly tested the effect of caffeine during a duo or team routine, and more elements are demanded during a duo/team presentation (e.g., teamwork and synchronization), caffeine-induced increases in flexibility, strength, power, and muscle endurance may help athletes to better perform difficult routines. This assumption is in agreement with several studies showing that caffeine has ergogenic effects in several sports demanding multiple physical capacities such as volleyball (35), basketball (36,37), and football (38).…”
Section: Discussionsupporting
confidence: 92%
“…Although we have not directly tested the effect of caffeine during a duo or team routine, and more elements are demanded during a duo/team presentation (e.g., teamwork and synchronization), caffeine-induced increases in flexibility, strength, power, and muscle endurance may help athletes to better perform difficult routines. This assumption is in agreement with several studies showing that caffeine has ergogenic effects in several sports demanding multiple physical capacities such as volleyball (35), basketball (36,37), and football (38).…”
Section: Discussionsupporting
confidence: 92%
“…We collected mean and error values only for the female group after contacting the corresponding authors of two of the studies [14,35]. We did not include two studies [36,37] that presented both sexes because the corresponding authors confirmed that they involved the same participants and tests that were presented in the following two studies that were included in the meta-analysis [32,38]. We did not contact the authors of one study that analyzed males and females together [13] because the measured main outcomes of the study were not of interest for the present review and meta-analysis.…”
Section: Meta-analysesmentioning
confidence: 99%
“…In addition, the hypoalgesic effect of caffeine decreases the perception of pain and effort during exercise and therefore might also be considered as a supplementary mechanism of action, at least for exercise situations that induce pain [3,12]. As a result, lower pain perception could maintain or increase the firing rates of the motor units and possibly produce a more sustainable and forceful muscle contraction, and consequently, allow greater strength production [3,14].…”
Section: Introductionmentioning
confidence: 99%